PERKEMBANGAN SENI REOG PONOROGO SINGO MANGGOLO MEKARSARI DI DESA TITIAN RESAK KECAMATAN SEBERIDA KABUPATEN INDRAGIRI HULU 1985-2019 - Herlina Evi Megawati; Bedriati Ibrahim; Asyrul Fikri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Reog Ponorogo is a barongan art originating from Ponorogo, East Java, which is spread throughout Indonesia, one of which is in Titian Resak Village, Seberida District, Indragiri Hulu Regency. Riau. The research objectives are as follows: (1) To determine the early history of the formation of the Reog Ponorogo Singo Manggolo Mekarsari Art in Titian Resak Village. (2) To determine the development of the Art of Reog Ponorogo Singo Manggolo Mekarsari in 1985-2019. (3) To find out the procession of the Reog Ponorogo Singo Manggolo Mekarsari performing arts. (4) To find out the values contained in the Reog Ponorogo Singo Manggolo art performance. (5) To find out the efforts of the community and local government in preserving the Reog Ponorogo Singo Manggolo Art. The method used is the historical method: (1) Heuristic. (2) Verification. (3) Interpretation. (4) Historiography. With the results of the research: The history of the formation of the Reog Ponorogo Singo Manggolo Mekarsari Art Association began with the arrival of the transmigration community in 1981 to Titian Resak Village, and the association was formed in 1985 on behalf of the community. Until now, it continues to develop until now, although it has stopped performing performances for 14 years due to social deviations and the entry of keyboard music. In 2009 a new management was formed with many changes in terms of music, clothing, songs and dances and included many moral values, educational values, cultural values and religious values in each appearance. Smoothness in appearance cannot be separated from the exercises that are carried out regularly and supporting musical instruments and properties. The community and government play an important role in preserving Reog Ponorogo art by making Reog Ponorogo art a regular performer in Village events. Thus, Titian Resak Village and Reog Ponorogo art are increasingly recognized by many people. Key Words: History, development, art, Reog Ponorogo Singo Manggolo Mekarsari, Titian Resak